Shifting Neighbourhood Dynamics and Everyday Experiences of Displacement in Kreuzberg, Berlin - Crowe, Adam (Curtin University, 2020)
This thesis explores the socio-spatial impacts of shifting housing and neighbourhood dynamics in the gentrifying neighbourhoods of Kreuzberg, Berlin. Using a multi-method approach, the qualitative-driven inquiry illuminates a range of shelter and non-shelter aspects of displacement impacting on long-standing residents’ relationships to the place they call home. At its core, this thesis underscores the longer temporal and psycho-social dimensions of residential displacement rarely considered in research on gentrification and tourism in the post-industrial city.